Engaging female community health volunteers in maternal health services and its satisfaction among village mothers in Hill and Mountain Regions, Nepal - Mina Lee (AIMS Press, 2020)
Background Female Community Health Volunteers (FCHVs) are service providers and educators for maternal health at the village level (in the hill and Terai district) in Nepal. At present, there are insufficient data and little is understood about the maternal health service (MHS) of FCHVs from Nepali mothers' perspective. Methodology The research was undertaken in three hill and mountain regions where there should be at least one FCHVs per ward, Thulo sirubari, Sano sirubari and Jalkeni in Chautara Sangachowkgadi in Nepal, during five days from 5 April to 9 April 2019. The study worked with a local partner organisation, Green Tara Nepal (GTN). The study took the form of a qualitative approach with a community-based snowball approach (seed-and-recruit approach), which consisted of interviews with six key informants and 11 village mothers who have a child aged under five. Results The study found that all participated mothers recognised FCHVs and that it was easy to contact them within walking distance. They were happy with FCHV's existence and had a close relationship between them. They were all satisfied with MHS from FCHVs. In particular, accessibility of FCHVs, frequent home visits, monthly mothers' meetings, and regular ANC were the main points of satisfaction. Moreover, NGO intervention increased their satisfaction and contributed significantly to FCHV activities. However, the lack of meeting place and sustainable incentives are challenging to implement monthly mothers' meetings. Sufficient regular refresher training for FCHVs is also required to educate them better. Furthermore, the local government's unequally distributed budget for FCHVs programmes, small incentives, and benefits for FCHVs are challenges. Conclusion This study offered various views with vivid memories into the satisfaction of FCHV's MHS among village mothers in three hill and mountain regions of Nepal. FCHVs are essential assets for MHS in rural communities. The FCHVs programme should be complemented by (1) supporting suitable meeting place of mother's meeting, (2) providing sustainable and sufficient budget for mother's meeting and FCHVs, (3) distributing the budget equally in each ward, (4) offering frequent FCHVs training to improve the MHS for village mothers.